2019
DOI: 10.1039/c9ra05581a
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Ag decorated CdMoO4 as an efficient photocatalyst for solar hydrogen production

Abstract: Plasmonic enhancement of photocatalytic hydrogen generation is demonstrated using hierarchical Ag decorated CdMoO4 synthesized using a hydrothermal method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…[ 20 , 21 ] On the other hand, the XRD pattern of CdO clearly displayed five very strong diffraction peaks at 2θ=33.07° (111), 38.34° (200), 55.30° (220), 65.96° (311) and 69.26° (222) which belong to face‐centred system (Monteponite CdO, JCPDS # 5‐0640) as shown in Figure 1 e.[ 22 , 23 ] Three distinct diffraction peaks can be observed in patterns b‐d of mixed MoO 3 ‐CdO samples at 2θ=29.25° (112), 31.99° (004) and 34.38° (200), which could be related to the formation of tetragonal phase CdMoO 4 in these mixtures (JCPDS # 07–0209). [ 24 , 25 , 26 ] The crystallite size of the obtained different phases in these samples, that is, α‐MoO 3 , CdO and CdMoO 4 , was calculated using the Scherrer equation. [22] For MoO 3 in all patterns a‐d, the full width at half maximum (FWHM) of the narrow Debye–Scherrer line at 2θ=27.30° was used to calculate the crystallite size of MoO 3 , revealing a size range of 65–80 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 20 , 21 ] On the other hand, the XRD pattern of CdO clearly displayed five very strong diffraction peaks at 2θ=33.07° (111), 38.34° (200), 55.30° (220), 65.96° (311) and 69.26° (222) which belong to face‐centred system (Monteponite CdO, JCPDS # 5‐0640) as shown in Figure 1 e.[ 22 , 23 ] Three distinct diffraction peaks can be observed in patterns b‐d of mixed MoO 3 ‐CdO samples at 2θ=29.25° (112), 31.99° (004) and 34.38° (200), which could be related to the formation of tetragonal phase CdMoO 4 in these mixtures (JCPDS # 07–0209). [ 24 , 25 , 26 ] The crystallite size of the obtained different phases in these samples, that is, α‐MoO 3 , CdO and CdMoO 4 , was calculated using the Scherrer equation. [22] For MoO 3 in all patterns a‐d, the full width at half maximum (FWHM) of the narrow Debye–Scherrer line at 2θ=27.30° was used to calculate the crystallite size of MoO 3 , revealing a size range of 65–80 nm.…”
Section: Resultsmentioning
confidence: 99%
“…[22,23] Three distinct diffraction peaks can be observed in patterns b-d of mixed MoO 3 -CdO samples at 2θ = 29.25°(112), 31.99°(004) and 34.38°( 200), which could be related to the formation of tetragonal phase CdMoO 4 in these mixtures (JCPDS # 07-0209). [24][25][26] The crystallite size of the obtained different phases in these samples, that is, α-MoO 3 , CdO and CdMoO 4 , was calculated using the Scherrer equation. [22] For MoO 3 in all patterns a-d, the full width at half maximum (FWHM) of the narrow Debye-Scherrer line at 2θ = 27.30°was used to calculate the crystallite size of MoO 3 , revealing a size range of 65-80 nm.…”
Section: X-ray Diffraction Measurementsmentioning
confidence: 99%
“…The basic photocatalytic mechanism was discussed in our previous study. 41 The surface of semiconducting materials, when exposed to visible light equal to or greater than the band gap energy, generates electrons in the conductance band (CB) and holes in the valence band (VB) by excitation from the VB to the CB. The holes from the VB oxidize methanol and produce radicals as well as protons (H + ).…”
Section: Resultsmentioning
confidence: 99%
“…Their study revealed the superior HER activity achieved using nanoscale silver particles over their macroscale counterparts 39 . Moreover, the HER at a silver nanoparticle‐decorated materials has also been the topic of many studies 40‐44 . Ni catalysts alone are not able to meet the desired activity, efficiency, and stability requirements for hydrogen production.…”
Section: Introductionmentioning
confidence: 99%
“…39 Moreover, the HER at a silver nanoparticle-decorated materials has also been the topic of many studies. [40][41][42][43][44] Ni catalysts alone are not able to meet the desired activity, efficiency, and stability requirements for hydrogen production. A combination of Ni and Ag metals has a synergistic effect enhancing the catalytic activity toward HER.…”
Section: Introductionmentioning
confidence: 99%